(untitled) (Journal of Global Arts Studies, 2024)
Background: The square space of stamps records the customs and historical footsteps of a country, so stamps are also known as "national business cards". Diving is a graceful water sport with a long history. Modern diving emerged in Europe from the late 19th century to the early 20th century. At the beginning of the 20th century, modern diving was introduced to China. At the beginning of the establishment of the People’s Republic of China, diving had rapidly developed with strong support from the country and the joint efforts of the people of the whole country. After years of hard work, the Chinese diving team has become the world leader in diving has won honors for Chinese sports and inspired more people to participate in this sport. Diving is widely loved in China, so it has repeatedly appeared on China’s "national business card". These stamps demonstrate the spirit of athletes striving to unleash their maximum potential and strive for the best results. Diving has appeared on Chinese stamps many times. The issuance of stamps shows the competitive and artistic beauty of diving. These stamps are brightly colored, dynamic and artistic. They are deeply loved by stamp collectors. Objective: Researcher has described the development process of diving in China by studying stamps issued in China after the 1980s. Methods: This article explores the artistic style of stamps by sorting them out, and outlines the development trend of diving in China since the 1980s from a historical viewpoint. Results: Through the organic combination of theory and practical cases, practical operations under various music teaching scenarios were designed. Conclusion: Since the 1980s, diving has been continuously developing in China and rapidly internationalizing with China’s return to the Olympic stage, affecting the design style of stamps, making them more historically and realistically significant, adding more international elements, enhancing the appreciation of stamps, making stamp patterns more dynamic, and increasing the value of stamp collection.